Clinical Predictors of Pseudomonas aeruginosa Bacteremia in Emergency Department - Yongsoon Choi; Jin Hui Paik; Ji Hye Kim; Seung Baik Han; Areum Durey (Emergency Medicine International)
Objectives. Pseudomonas aeruginosa shows higher mortality rate compared to other bacterial infections and is susceptible to a limited number of antimicrobial agents. Considering inadequate empirical treatment of Pseudomonas bacteremia has been associated with increased mortality, it is important for emergency physicians to identify infections by P. aeruginosa. Methods. This was a single-center retrospective case-control study to investigate the clinical predictors of patients diagnosed as Pseudomonas bacteremia in the emergency department (ED) from June 2012 to December 2016. Patients with blood culture positive for Escherichia coli in the same period were chosen as the control group, and type of infection was matched for each patient. Results. A total of 54 cases with Pseudomonas bacteremia and 108 controls with E. coli bacteremia were included. In the case group, 76% was community-acquired infection, 44% received inappropriate empirical treatment in the ED, and in-hospital mortality was 30%. Multiple logistic regression showed that respiratory tract infection was an independent risk factor for Pseudomonas bacteremia (OR 6.56, 95% CI 1.78-23.06; p = 0.004), whereas underlying diabetes mellitus (OR 0.22, 95% CI 0.07-0.61; p = 0.004) and presentation as urinary tract infection (OR 0.06, 95% CI 0.02-0.18; p < 0.001) were negative clinical predictors. Conclusions. We suggest that antipseudomonal antibiotics should be considered beyond simple coverage of Gram-negative bacteria in the ED, especially if the patient is likely to have pneumonia. Having diabetes or presenting with urinary tract infection could be clinical factors unfavorable to use of antipseudomonal antibiotics.